An evaluation of the ability of Dichelobacter nodosus to survive in soil - Cederlöf Sara Ellinor; Hansen Tomas; Klaas Ilka Christine; Angen Øystein (Acta Veterinaria Scandinavica, 2013)
Abstract Background Dichelobacter nodosus is the causative agent of footrot in sheep. The survival of the bacterium in soil is of importance for the epidemiology of the disease. The investigation evaluates the survival of D. nodosus in soil with and without added hoof powder stored under different temperatures. Results An experimental setup was used with bacteriological culture and real-time polymerase chain reaction (PCR), and the results indicate that the bacteria can survive in soil for longer time than previously expected. The survival time was found to be dependent on temperature and the addition of hoof powder to the soil, with the longest survival time estimated to be 24 days in soil samples with hoof powder stored at 5°C. Conclusion Our findings indicate that the survival time of D. nodosus and its ability to infect susceptible sheep on pasture under different climatic conditions should be studied further.